Pengaruh Rasio Profitabilitas, Leverage Dan Aktivitas Terhadap Pertumbuhan Laba (Studi Empiris Pada Perusahaan Yang Terdaftar Pada Indeks IDX30 Di Bursa Efek Indonesia Periode 2013-2018) - Indri Oktaviani; Asep Muslihat; Gus Ganda Suria Manda (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This study aims to determine the effect of profitability on profit growth, the effect of leverage on profit growth, the effect of activity on profit growth and the effect of profitability, leverage and activity on profit growth in companies listed on the IDX30 Index on the Indonesia Stock Exchange 2013-2018. This study uses secondary data with the 2013-2018 research period. The data used comes from the annual financial statements of companies listed on the IDX30 Index on the Indonesia Stock Exchange for the period 2013-2018. The population in this study consisted of 30 companies listed on the IDX30 Index on the Indonesia Stock Exchange. In this study, there were 13 sample companies with purposive sampling technique. The data analysis method used is multiple linear regression analysis. Data were processed using SPSS 25 software. The results of this study indicate that: (1) profitability has no significant effect on profit growth (2) leverage has a significant effect on profit growth (3) activity does not have a significant effect on profit growth (4) profitability, leverage and activity have a significant effect on profit growth. Keywords: Profitability, Leverage, Activity, Profit Growth